Social Exclusion, Deprivation and Marginalization of Females of Jammu and Kashmir - lone, Adil majeed (IJRDO- Journal of Educational Research, 2017)
This paper traces the trajectory of women’s socio-economic and educational status in the state of Jammu and Kashmir. Women constitute almost half of the total human resources (population) of Jammu and Kashmir. Unfortunately, denial of equal socio-economic opportunities and strong traditional bias against women have resulted in low human development indices over the years, as Jammu and Kashmir , like many other states, has lagged behind in upgrading the status of half of its women, in many respects. Education is universally accepted as a fundamental agent of socio-economic upliftment but women have not been fairly treated as far as access to education is concerned. It is needless to emphasize that education for women is synonymous to health, information, confidence, dignity, empowerment and independence. Conversely, illiteracy leads to their exploitation in all walks of life. Despite the fact that women’s education in Jammu and Kashmir has been a major area of concern for both the government and civil society and some statistics have changed since independence, though many ground realities have not. Gender bias against women and hence, gender gap still persists in almost all aspects of women education and we are far behind a condition where ‘educating women’ is no longer a news. The present paper discusses the trail of progress and current educational status of women in the state.